Meta-analysis of average costs of HIV testing and counselling and voluntary medical male circumcision across thirteen countries. Issue 4 (6th December 2019) - Pineda-Antunez, Carlos; Martinez-Silva, Gisela; Cerecero-Garcia, Diego; Alexander, Lily; Cameron, Drew B; Chiwevu, Chris; Dandona, Lalit; Obure, Carol Dayo; Forsythe, Steven; Nguyen, Van Thu; Settumba, Stella; Tchuenche, Michel; et al.
Abstract : Objective: Explore facility-level average costs per client of HIV testing and counselling (HTC) and voluntary medical male circumcision (VMMC) services in 13 countries. Methods: Through a literature search we identified studies that reported facility-level costs of HTC or VMMC programmes. We requested the primary data from authors and standardised the disparate data sources to make them comparable. We then conducted descriptive statistics and a meta-analysis to assess the cost variation among facilities. All costs were converted to 2017 US dollars ($). Results: We gathered data from 14 studies across 13 countries and 772 facilities (552 HTC, 220 VMMC). The weighted average unit cost per client served was $15 (95% CI 12, 18) for HTC and $59 (95% CI 45, 74) for VMMC. On average, 38% of the mean unit cost for HTC corresponded to recurrent costs, 56% to personnel costs, and 6% to capital costs. For VMMC, 41% of the average unit cost corresponded to recurrent costs, 55% to personnel costs, and 4% to capital costs. We observed unit cost variation within and between countries, and lower costs in higher scale categories in all interventions.